# Order of Operations Addition Subtraction

**Introduction to operations:**

In this article we are going to see about the order of the operations. The operation here is considered as the arithmetic operation which is used to add, subtract and multiply the given numbers. There are some order that should be followed in the function of the addition and subtraction of numbers. Let us see about the order of operations in detail in this article.

## Order of Operations

**Order of operations:**

The order for doing the operations for the given expression contains some of the rules. The rules for performing the order of operations is given as,

- When the given expression is with parenthesis then we should do the operation that is given inside the parenthesis. That may be the addition or it maybe the subtraction operation.
- Then the next order is to do the given operations such as multiplication and division from the left side towards the right side.
- Allthe operations of the addition and subtraction is done in the last step. This operation of addition and subtraction is done by using the order from left towards the right.

## Example Problems

**Problem 1:** Evaluate 8+ (5-3).

**Step 1:** First we should do the subtraction which is given inside the parenthesis. That is we should subtract 5 and 3. So that we get the answer 2.

8 + ( 5 -3) = 8 +(2)

**Step 2:** Then we should perform the addition operation which is given here,

8 + (5 -3) = 8 +(2)

= 10.

Hence after evaluating the given expression we get the answer as 10.

**Problem 2:** Evaluate: (5 + 11) – 12

**Step 1:** First we should do the addition which is given inside the parenthesis. That is we should add 5 and 11. So that we get the answer as 16.

(5 + 11) – 12 = (16) – 12

**Step 2:** Then we should do the subtraction operation which is given as,

(5 + 11) – 12 = (16) – 12

= 4.

After evaluating the given expression we get the answer 4.

**Problem 3:** Evaluate 2 + 6 * ( 1+ 4) / 3 -7

**Step 1:** First we should do the operation within the parenthesis. So that,

2 + 6 * ( 1+ 4) / 3 -7 = 2+6*5/3-7

**Step 2:** Then we should do the multiplication operation which is given as,

2 + 6 * ( 1+ 4) / 3 -7 = 2+6*5/3-7

= 2 + 30/3-7

**Step 3: **Then we should do the division operation,

2 + 6 * ( 1+ 4) / 3 -7 = 2+6*5/3-7

= 2 + 30/3-7

= 2 + 10 – 7

**Step 4:** Then we should perform the addition operation which is given as,

2 + 6 * ( 1+ 4) / 3 -7 = 2+6*5/3-7

= 2 + 30/3-7

= 2 + 10 – 7

= 12 – 7

**Step 5: **Here we should do the subtraction operation and get the answer. Thus,

2 + 6 * ( 1+ 4) / 3 -7 = 2+6*5/3-7

= 2 + 30/3-7

= 2 + 10 – 7

= 12 – 7

= 5

Hence the answer after evaluating the expression is given as 5.